Analisis Adat Hole di Kabupaten Sabu-Raijua Menurut Hukum Pidana - Aplonia Duru Kana; Adrianus Djara Dima; Rosalind Angel Fanggi (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
Customs are eternal codes of conduct that are passed down from one generation to another as a legacy, so that they are strongly integrated with community behavior patterns. Hole is a traditional ceremony that is very popular among the people of Sabu-Raijua which is carried out en masse. But there are still many outsiders and also the people of Sabu Raijua who consider chicken spurs to be gambling. Indonesia is a country based on law, so that every human or community activity which is a life activity must be based on existing regulations and norms that apply in society. The formulation of the problem in this research is, based on the background description above, the main problem studied by the author is formulated as follows: Does the Hole custom conflict with the rules of Criminal Law? This research uses empirical legal research methods sourced from data obtained directly in the form of information and opinions from respondents, namely traditional elders and the community in Sabu-Raijua Regency. The results of the research show that the cockfighting ritual in the hole tradition is a tradition that has been passed down from generation to generation, which is a sacred ritual that conveys a message of peace to the next generation. They believe that if this ritual is not carried out then human life will be far from disputes and quarrels, humans will live in prosperity both with each other and with their ancestors as well as the land, the livestock they cultivate will give good results. However, in the last 2 years the cockfighting ritual is no longer just a tradition, because now people are using the Pei'uManu (Cockfighting) tradition as a means of gambling.